Yield enhancement of rapeseed-mustard through innovative transplanting technique in Assam - HV Singh,; AK Sharma,; Arun Kumar,; Vinod Kumar,; Pankaj Sharma,; MJ Nath,; M Danish,; PK Rai, (Journal of Oilseed Brassica, 2026)
A study was carried-out during winter season of 2022-23 at Bongaigaon and Dhubri districts of Assam to evaluate theyield performance of transplanted and broadcasted sowing methods of Toria (Brassica rapa ssp. Toria) and Indianmustard (Brassica juncea). Field experiments were laid down in randomized block design with five replications and fourtreatments including transplanted Toria, Toria broadcasting, transplanted mustard and mustard broadcasting. Resultsshowed that the transplanting of both Toria and mustard resulted the greater values of plant height, number of siliqua/plant, number of primary branches/ plant and number of secondary branches/ plant over the broadcast method ofsowing. The highest average seed yield was recorded in transplanted mustard (19.3 q/ha) followed by transplanted Toria(13.9 q/ha) which were recorded around 67 % and 49 % more yield as compared to broadcasted mustard and Toria,respectively. The additional net monetary return (32060 Rs./ha) and benefit cost ratio (3.2) were also recorded higher intransplanted mustard as compared to other treatments. From this study it can be concluded that the transplanting ofmustard and Toria could be beneficial for getting higher yield as well as additional net monetary returns as compared tobroadcasted sowing method in the Assam.